The Representations of Space of Human Trafficking for Sexual Exploitation in Argentina, at the Beginnings of the 21st Century - Moreno, Magdalena (2019)
The present paper analyzes the representations of space of human trafficking for sexual exploitation in Argentina, between 2008 and 2018. For this analysis, I worked with Lefebvre´s theory, especially with the three dimensional analysis of espatial production: spatial practices, representations of space and spaces of representation. I paid special attention to the second concept to interpret the mapping produced by Ministerio Público Fiscal (the ministry that is in charge of administers justice), the mass media and civil society organizations. The paper is organized in three moments. At first, it describes, briefly, Henri Lefebvre‘s conceptualization to analyze the spatiality and emphasizes the concept of representations of space. In a second moment, analyzes the mapping made to represent the phenomenon of human trafficking for sexual exploitation in Argentina.Then, a critical reading about this mapping is made and the spatiality that they create or construct is analyzed from a gender perspective. That perspective is required to do the analysis because it allows to visibilize the gender oppression at the sexual exploitation. In a third moment and to conclude, some questions are opened in relation to the possible geographical imaginaries that can be configured from the representations of the space of human trafficking of sexual exploitation in Argentina.